Anthropometric assessment of abdominal obesity and coronary heart disease risk in men: the PRIME study. Issue 2 (28th June 2009) - Gruson, E; Montaye, M; Kee, F; Wagner, A; Bingham, A; Ruidavets, J-B; Haas, B; Evans, A; Ferrières, J; Ducimetière, P P; Amouyel, P; Dallongeville, J
Abstract : Objective: Waist-to-height ratio is an anthropometric indicator of abdominal obesity that accounts for stature. Earlier studies have reported marked associations between the waist-to-height ratio and cardiovascular risk factors. The goal of this study was to compare the associations of waist-to-height ratio, waist girth, waist-to-hip ratio or body mass index (BMI) with incidence of coronary events. Design: Prospective study with 10 602 men, aged 50–59 years, recruited between 1991 and 1993 in three centres in France and one centre in Northern Ireland. Clinical and biological data were obtained at interview by trained staff. During the 10 years of follow-up 659 incident coronary events (CHD) were recorded. The relations between anthropometric markers and coronary events were estimated by Cox proportional hazards models. Results: Waist circumference, waist-to-hip ratio, waist-to-height ratios and BMI were positively associated with blood pressure (p<0.0001), diabetes (p<0.0001), low-density lipoprotein (LDL)-cholesterol (p<0.0001), triglycerides (p<0.0001) and inversely correlated to high-density lipoprotein (HDL)-cholesterol (p<0.0001). There was a linear association between waist circumference, waist-to-hip ratio, waist-to-height ratio, BMI and CHD events. The age-adjusted and centre-adjusted relative risks (95% CI) for CHD were 1.57 (1.22 to 2.01), 1.75 (1.34 to 2.87), 2.3 (1.79 to 2.99) and 1.99 (1.54 to 2.56) in the 5th quintile vs the first quintile of waist circumference, waist-to-hip ratio, waist-to-height ratio and BMI distribution, respectively. After further adjustment for school duration, physical activity, tobacco and alcohol consumption, hypertension, diabetes, HDL-cholesterol and triglycerides, the relative risks for CHD were 0.99 (0.76 to 1.30) for waist circumference (p = 0.5), 1.22 (0.93 to 1.60) for waist-to-hip ratio (p = 0.1), 1.53 (1.16 to 2.01) for waist-to-height ratio (p = 0.03) and 1.30 (0.99 to 1.71) for BMI (p = 0.06). Conclusion: In middle-aged European men, waist-to-height ratio identifies coronary risk more strongly than waist circumference, waist-to-hip ratio or BMI, though the difference is marginal.